History of Mathematics Teaching and Learning Achievements, Problems, Prospects - Karp, Alexander; Furinghetti, Fulvia (ICME-13 Topical Surveys, 2016)
This work examines the main directions of research conducted on the history of mathematics education. It devotes substantial attention to research methodologies and the connections between this field and other scholarly fields. The results of a survey about academic literature on this subject are accompanied by a discussion of what has yet to be done and problems that remain unsolved. The main topics you will find in "ICME-13 Topical Survey" include: • Discussions of methodological issues in the history of mathematics education and of the relation between this field and other scholarly fields. • The history of the formation and transformation of curricula and textbooks as a reflection of trends in social-economic, cultural and scientific-technological development. • The influence of politics, ideology and economics on the development of mathematics education, from a historical perspective. • The history of the preeminent mathematics education organizations and the work of leading figures in mathematics education. • Mathematics education practices and tools and the preparation of mathematics teachers, from a historical perspective.